Double Negation, Excluded Middle and Accessibility in Dynamic Semantics - Gotham, Matthew (Proceedings of the Amsterdam Colloquium, 2019)
This paper addresses a recalcitrant problem for dynamic semantics: the inaccessibility of discourse referents from under double negation or from a negated left disjunct into a right disjunct. I propose that these discourse referents are made accessible by the discourse being interpreted in the context of designated formulae, which validate double negation elimination in a controlled way.